Communication process between the commercial sector of Medellín and China: importer-exporter relationship in toy stores of “el hueco” sector (2021)
In this paper you will find a study about the communication process used in the commercial exchanges in Toy Stores of “El Hueco” sector of the city of Medellin with Chinese exporters. To accomplish this aim, the research was focused on a qualitative design, regarding that it was necessary the analysis of the persons and undertakings involved in a negotiation, analyzing the influence of protocols and etiquette when trading with China. Expecting to find a steady process within the companies but, instead of that, the result of the surveys was as diverse as the market itself.